Nurcholish Madjid's Inclusive Preaching Paradigm. - Rustam, Ahmad S.; Hamidun, Hamidun (Jurnal Mercusuar, 2020)
Dakwah is still a discourse that deserves to be discussed by various Muslim groups in Indonesia, because there is a fundamental basis that drives us to carry out the duty of dakwah, namely the Quran and Sunnah. Conceptually, everything starts from the same aspect, and therefore our effort is to translate each normative command into implementation in today's society. Finding the right and appropriate method for the current era is a necessity for us so that Islamic dakwah can be accepted well and correctly.